Interest Rate: Zero (Observatorio Económico, 2009)
So what will the Central Bank of Chile do to keep the economy going if interest rates cannot fall any further? The Economist explains this point well: that is when the era of unconventional measures begins, such as the desperate issuance of money to sustain the economy's liquidity at all costs. Continue reading...
Keywords: zero interest rate; Central Bank of Chile